2014
DOI: 10.1038/cgt.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN reduction via scFv-M6-1B9 intrabody affects α3β1-integrin and MCT1 functions and results in suppression of progressive phenotype in the colorectal cancer cell line Caco-2

Abstract: Extracellular matrix metalloproteinase inducer (EMMPRIN) exhibits overexpression in various cancers and promotes cancer progression and metastasis via the interaction with its associated molecules. The scFv-M6-1B9 intrabody has a potential ability to reduce EMMPRIN cell surface expression. However, the subsequent effect of scFv-M6-1B9 intrabody-mediated EMMPRIN abatement on its related molecules, α3β1-integrin, MCT1, MMP-2 and MMP-9, is undefined. Our results demonstrated that the scFv-M6-1B9 intrabody efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…[39][40][41] CFs produce a variety of cytokines, such as IL-6, endothelin-1, and insulin-like growth factor-1, all of which induce hypertrophic response in cardiomyocytes in a paracrine manner. 40,42,43 In this study, we demonstrated that cell surface Bsg is cleaved and secreted from CFs in response to stimulus by mechanical stretch and Ang II. Moreover, treatment with hrBsg activated mitogen-activated protein kinase in CFs and promoted cell proliferation.…”
Section: Inflammatory Response Of Cfs To Pressure Overloadmentioning
confidence: 59%
“…[39][40][41] CFs produce a variety of cytokines, such as IL-6, endothelin-1, and insulin-like growth factor-1, all of which induce hypertrophic response in cardiomyocytes in a paracrine manner. 40,42,43 In this study, we demonstrated that cell surface Bsg is cleaved and secreted from CFs in response to stimulus by mechanical stretch and Ang II. Moreover, treatment with hrBsg activated mitogen-activated protein kinase in CFs and promoted cell proliferation.…”
Section: Inflammatory Response Of Cfs To Pressure Overloadmentioning
confidence: 59%
“…In our study, we demonstrated earlier that chimeric adenovirus 5/F35 carrying gene encoding scFv against EMMPRIN (Ad5/F35- scFv-M6-1B9 ) is effective in diminishing EMMPRIN cell surface expression and subsequently decreasing cancer cell proliferation, invasion, and metastasis in the colorectal cancer cell line, Caco-2 31 . However, the apoptotic effect of reducing EMMPRIN cell surface levels using intrabody technique in established colorectal cancer cells has hitherto been unclear.…”
Section: Introductionmentioning
confidence: 64%
“…Our previous study revealed for the first time that scFv-M6-1B9 intrabody has the ability to down-regulate EMMPRIN cell surface expression on colorectal cancer cell, Caco-2, via flow cytometry 31 . To confirm the reduction of the EMMPRIN cell surface expression due to its accumulation inside the cells, immunoblotting was performed.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, siRNA targeting CD147 inhibits the invasion of human cervical squamous carcinoma cells [103]. The intrabody scFv-M6-1B9 can reduce CD147 cell surface expression in a colorectal cancer cell line (Caco-2), which leads to subsequent suppression of tumor progression, including cell migration, proliferation and invasion [104]. Therefore, agents such as antisense RNAs, intrabody and antibody drugs against CD147 that intervene in CD147 functions may have possible therapeutic effects in the prevention and treatment of glioma progression.…”
Section: Resultsmentioning
confidence: 99%